Studies on the Balance between Thrombomodulin and HMGB1 in Sepsis Patients - Adriana Teixeira Rodrigues; Julia Teixeira Rodrigues; Carolina Teixeira Rodrigues; Jose Augusto Nogueira-Machado; Luiz Ronaldo Alberti (Highlights on Medicine and Medical Science Vol. 7, 2021)
Background: The balance between high mobility group box 1 (HMGB1) and thrombomodulin (TM) in sepsis patients needs to be understood. HMGB1 has been studied as a molecule associated with severe outcomes in sepsis and thrombomodulin (TM) seems to have an anti-inflammatory effect. Aim: To describe the balance between high mobility group box 1 protein (HMGB1) and thrombomodulin (TM) in early sepsis and their association with clinic presentation and outcomes. Methods: Twenty patients diagnosed with sepsis or septic shock were studied according to the 2016 criteria (SEPSIS-3). Patients were followed up until they left the intensive care unit (ICU) or until 28 days in hospital (D28). The following clinical results were observed: Sequential Organ Failure Assessment (SOFA) Score; time in mechanical pulmonary ventilation (MV); severity of hypoxemia; presence of septic shock; occurrence of sepsis-induced coagulopathy (SIC); need for renal replacement therapy (RRT); and death. The results showed a positive correlation between serum TM levels and the T / H ratio with SOFA score values, r = 0.64 and 0.6. The T / H ratio showed a positive correlation with time in MV and a negative one with the degree of hypoxemia (r = 0.35 and - 0.39, respectively). Serum TM levels were positively related to the INR values and negatively to the platelet count values (r = 0.53 and - 0.47, respectively). Higher values of TM and T / H ratio were associated with the presence of CIS (p = 0.007 and 0.034, respectively). The T / H ratio was, on average, three times higher in patients in need of RRT (0.38 ± 0.14 vs 0.11 ± 0.09), p <0.001. Conclusions: Although the serum level of HMGB1 in the first 24 hours of diagnosis was not associated with greater severity of sepsis, the serum levels of TM in the first 24 hours were. Higher serum levels of TM and, consequently, a higher T / H ratio were related to higher scores on the SOFA score, longer MV time and more severe hypoxemia, in addition to being associated with the presence of CIS and the need for RRT. On the other hand, patients who were discharged before 28 days showed a tendency to lower T / H ratios.